The effect of volume change and stack pressure on solid-state battery cathodes - Liu, B; Pu, SD; Doerrer, C; Spencer Jolly, D; House, RA; Melvin, DLR; Adamson, P; Grant, PS; Gao, X; Bruce, PG (Wiley, 2023)
Solid-state lithium batteries may provide increased energy density and improved safety compared with Li-ion technology. However, in a solid-state composite cathode, mechanical degradation due to repeated cathode volume changes during cycling may occur, which may be partially mitigated by applying a significant, but often impractical, uniaxial stack pressure. Herein, we compare the behavior of composite electrodes based on Li4Ti5O12 (LTO) (negligible volume change) and Nb2O5 (+4% expansion) cycled at different stack pressures. The initial LTO capacity and retention are not affected by pressure but for Nb2O5, they are significantly lower when a stack pressure of <2 MPa is applied, due to inter-particle cracking and solid-solid contact loss because of cyclic volume changes. This work confirms the importance of cathode mechanical stability and the stack pressures for long-term cyclability for solid-state batteries. This suggests that low volume-change cathode materials or a proper buffer layer are required for solid-state batteries, especially at low stack pressures.